1998
DOI: 10.1163/22941932-90001533
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of the Secondary Deposition of Incrusting Materials on Bordered Pit Membranes in Cryptomeria Japonica

Abstract: Bordered pit membranes of Cryptomeria japonica were examined successively from the outermost sapwood to the heartwood by scanning electron microscopy and by ultraviolet microspectrophotometry in an attempt to evaluate the time course of the secondary deposition of incrusting materials and to gain clues to their chemical composition. Scanning electron microscopy revealed that the bordered pit membranes were covered by incrusting materials from the middle layer of the sapwood to the heartwood. Both the amount an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…Sections (1 m) were cut with a glass knife on an ultramicrotome (Ultracut N; Reichert), placed on quartz slides, mounted in glycerin with quartz coverslips, and observed with an UV microscope (MPM800; Carl Zeiss, Oberkochen, Germany). UV micrographs were taken on conventional black-andwhite Wlm (Neopan 100 Across; FujiWlm, Tokyo Japan) at 280 nm with a 5-nm wavelength range (Sano and Nakada 1998;Takabe 2002;Yoshida et al 2005;Watanabe et al 2006).…”
Section: Uv Microscopymentioning
confidence: 99%
“…Sections (1 m) were cut with a glass knife on an ultramicrotome (Ultracut N; Reichert), placed on quartz slides, mounted in glycerin with quartz coverslips, and observed with an UV microscope (MPM800; Carl Zeiss, Oberkochen, Germany). UV micrographs were taken on conventional black-andwhite Wlm (Neopan 100 Across; FujiWlm, Tokyo Japan) at 280 nm with a 5-nm wavelength range (Sano and Nakada 1998;Takabe 2002;Yoshida et al 2005;Watanabe et al 2006).…”
Section: Uv Microscopymentioning
confidence: 99%
“…Additionally, Putoczki et al (2008) showed abundant deposition of unesteriWed and methyl-esteriWed pectic polysaccharides in bordered pit membranes of radiata pine. Although several studies have reported the presence of phenolic compounds in bordered pit membranes of softwood (Bauch et al 1968;Bauch and Berndt 1973;Sano and Nakada 1998), the presence of lignin in pit membranes in softwoods is still not clear.…”
Section: Introductionmentioning
confidence: 97%
“…Bland and Hillis 1969;Hillis et al 1976;Imagawa and Fukazawa 1978;Kleist and Bauch 2001) and (v) the chemical composition of pit membranes of gymnosperms (e.g. Bauch and Berndt 1973;Sano and Nakada 1998). All these investigations were performed by UV microscopic point measurements using a spot size of l µm 2 of cell wall area or two dimensional UV scanning profiles across the cell wall width as shown by Bauch et al (1976).…”
Section: Introductionmentioning
confidence: 99%